Meningkatkan Hasil Belajar Kebugaran Jasmani Melalui Metode Role Playing Pada Siswa Kelas VI Sdn Ngronggo 5 - Emha Faisal Yusuf; Puspodari Puspodari; Anggi Kurniasari (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to improve physical fitness learning outcomes through the implementation of the role-playing method in sixth-grade students at SDN Ngronggo 5. The research employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, conducted over two cycles. The subjects were 30 students, with data collected through observation, questionnaires, and achievement tests. The results indicated that the role-playing method effectively increased students' active participation in learning activities and had a positive impact on improving physical fitness learning outcomes. This improvement was evident in the comparison between pre-test and post-test scores, which showed a significant increase after applying the method. Additionally, students demonstrated enthusiasm and good cooperation throughout the learning process. In conclusion, the role-playing method is an effective active learning strategy for physical education subjects in elementary schools.